2013
DOI: 10.1186/1471-2318-13-66
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status of older adults of diverse ancestry living in the greater Toronto area

Abstract: BackgroundPhysiological and lifestyle factors put older adults at an increased risk of vitamin D insufficiency and resulting negative health outcomes. Here we explore the vitamin D status in a sample of community dwelling older adults of diverse ancestry living in the Greater Toronto area (GTA).MethodsTwo hundred and twenty-four (224) adults over 60 years of age were recruited from the Square One Older Adult Centre, in Mississauga, Ontario. Circulating 25-hydroxyvitamin D (25(OH)D) concentrations were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
2
11
1
4
Order By: Relevance
“…Among HF patients, the number of men with vitamin D deficiency were significantly more than women. This finding adjusts with the results of one study (19) and is contrast with other ones (18,20). The reason may be a more disease severity among men compared to women.…”
Section: Discussionsupporting
confidence: 70%
“…Among HF patients, the number of men with vitamin D deficiency were significantly more than women. This finding adjusts with the results of one study (19) and is contrast with other ones (18,20). The reason may be a more disease severity among men compared to women.…”
Section: Discussionsupporting
confidence: 70%
“…Além disso, os membros voluntários do estudo provavelmente representam a parcela que valoriza o envelhecimento saudável, preocupada com os benefícios da vitamina D e que já faziam essa suplementação. 9 Aspectos relacionados à aderência ao tratamento também não puderam ser controlados. O uso de determinadas medicações, a presença de comorbidades ou o uso prévio de suplementação de vitamina D, que podem interferir no metabolismo da vitamina D, não foram critérios de exclusão, pois a intenção dos pesquisadores foi retratar da forma mais próxima possível a realidade da população para a qual a SES/ DF deve programar a política de saúde.…”
Section: Discussionunclassified
“…Para isso, são necessárias doses diárias entre 1.000 e 2.000 UI. 3,9 A vitamina D pode ser administrada diariamente, semanalmente, mensalmente, trimestralmente ou semestralmente. 3,5,9 Não parece haver diferença na absorção da vitamina D considerando-se o tipo de refeição ou jejum.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Ginter and cols. (21), in a study of 224 elderly patients (> 60 years), showed a prevalence of vitamin D deficiency (< 30 ng/mL) of 40% (44°N). In this sample, individuals from three different eth nic groups were evaluated with no significant differences being found between them.…”
Section: Ethnicity and Vitamin D Deficiency Abroadmentioning
confidence: 99%